The Effect of Good Corporate Governance on Capital Structure With Company Size As A Moderating Variable - Mais, Rimi Gusliana; Ainun Komala Indah (LPPM Universitas Terbuka, 2023)
The purpose of this study is to obtain empirical evidence on the effects of institutional ownership, managerial ownership, and board size on capital structure by considering firm size as a moderating variable. The research is conducted through the website www.idx.co.id, during the period 2018-2021 he surveyed 23 companies in the real estate and real estate sector listed on IDX, the research period is his four years. Aggregated data is used by 92 companies that process data using Eviews. Research has shown that management ownership and board size have a positive impact on capital structure. Firm size can relax the relationship between institutional and managerial ownership in the capital structure. Institutional ownership does not affect the capital structure. The study also found that firm size does not mitigate the impact of board size on capital structure. The number of directors' meetings in this study had no effect so this could have happened because during a board of directors' meeting they could not be responsible for determining whether management had fulfilled its responsibilities and exercised control. especially in minimizing the use of debt in the capital structure and governance control of property and real estate companies.